Nilai-Nilai Pendidikan Humanistik Dalam Dakwah Sunan Drajat - Saifullah, Ahmad; Sukarman, Sukarman (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2023)
True education is a form of human effort to humanize humans, namely by cultivating or glorifying human life to develop human potential, and the socialization of skills must be passed through educational activities that uphold humanistic values (humanistic). In addition to the concept of humanistic education promoted by Western education figures, there is one legendary local figure who carries the value of humanistic education, namely Sunan Drajad. This study tries to explore the values of humanistic education from the da'wah method carried out by Sunan Drajad with a qualitative descriptive approach. This study concludes that the value of Sunan Drajad's humanistic education is reflected in the Pepali pitu philosophy